Building an archaeology of Maya urbanism: planning and flexibility in the American tropics - Marken, Damien B., editor; Arnauld, M. Charlotte, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
Building an Archaeology of Maya Urbanism tears down misconceptions of Maya cities, building a new archaeology of Maya urbanism, highlighting the dynamics of an ancient civilization of the Americas. Exploring agents and processes that modified Maya urban landscapes, this volume highlights the flexibility of urbanization in the Maya lowlands.--Provided by publisher.
Building an archaeology of lowland Maya urbanism / Damien B. Marken and M. Charlotte Arnauld -- The roots of urbanization: Early-Middle Preclassic transformations to a sedentary lifestyle at Ceibal, Guatemala / Daniela Triadan and Takeshi Inomata -- Living in a contested landscape: adapting settlement decisions in the Buenavista Valley, Petén, Guatemala / Thomas Garrison -- A city in flux: the dynamic urban form and function of El Perú-Waka' / Keith Eppich, Damien B. Marken and Elsa Damaris Menéndez -- Urbanizing paradise: the implications of pervasive images of flower world across Chichen Itza / Travis Stanton, Karl A. Taube, José Francisco Osorio León, Francisco Pérez Ruíz, and María Rocio González de la Mata -- Spatial and social contraction in Late-Terminal Classic Río Bec neighborhoods / M. Charlotte Arnauld and Sarah Dzul -- Households, neighborhoods, and inequality at two Classic Period Maya cities in Southern Belize / Amy E. Thompson and Keith M. Prufer -- Households, growth, contraction, and mobility at the Classic Maya Center of Naachtun / Julien Hiquet, Julien Sion and Divina Perla Barrera -- Walking through the urban maze of Mayapán / Timothy Hare and Marilyn Masson -- The living landscape: livelihoods and opportunities in the city and region of Ancient Tikal / Timothy Murtha -- Urban planning at Caracol: governance, residential autonomy, and heterarchical management through time / Adrian S. Z. Chase -- Urban planning through the prism of infrastructure at Palenque, Chiapas: an assessment of urban function and local decision-making during the Late Classic / r Rodrigo Liendo Stuardo and Arianna Campiani -- Settlement pattern and land use dynamics at Naachtun: shaping an agrarian Maya town / Phillipe Nondédéo, Eva Lemonnier, Julien Hiquet, Louise Purdue, Cyril Castanet, Lydie Dussol, and Marc Testé -- The death and life of agricultural cities / John Walker.
Keywords: Urban Mayas; Mayas -- Antiquities; Urbanization -- Central America